1936
DOI: 10.1021/ie50319a015
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Derris and Cube

Abstract: ECONOMICconsiderations lead to the use of powdered derris or cube, or extracts made from them, as insecticides instead of the highly active principles, rotenone and its relatives, which have been isolated from these plants. Although in the earlier studies of the action of derris it was believed that rotenone was the essential constituent, recent work (S, 5) has strengthened the view that the roots of derris and cube possess more insecticidal activity than can be accounted for by their rotenone content. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1938
1938
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mathews and Lightbody (273) in 1936 reported on the toxicity of three samples of derris and one of cube to rats.…”
Section: Pharmacology Of Lonchocarpusmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathews and Lightbody (273) in 1936 reported on the toxicity of three samples of derris and one of cube to rats.…”
Section: Pharmacology Of Lonchocarpusmentioning
confidence: 99%
“…McKinncy (273) in September 1936 reported that the application of dust mixtures containing 1 percent rotenone, derived from derris or cube, with talc as a diluent, proved effective in controlling the western striped cucumber beetle, Diabrotica trivittata Mann., on cantaloupes in the Salt River Valley, Ariz.…”
Section: Use Of Lohdhocjffus As Ai\ T Insecticidementioning
confidence: 99%